A SUGGESTED DESIGN APPROACH FOR BUILT-UP COLD-FORMED COLUMNS BASED ON RESEARCH USING NONLINEAR FINITE ELEMENT METHOD - (:unkn) unknown (My University, 2011)
A deficiency of the 2007 AISI specification, Sections C4 and D1.2 for built-up, coldformed

members under pure compression is experimentally identified. The AISI specification

is found to be exceedingly conservative, especially for distortional-buckling members

with a larger cross section and a longer length. By using sequential batch-feeding,

nearly a thousand nonlinear-buckling finite element simulations of built-up, cold-formed

sections are carried out to validate the model prior to experimental work, identify the extent

of the deficiency, and rectify the deficiency. In all, a simpler less-conservative design

equation for cold-formed built-up members prone to distortional buckling is proposed in

this two-phase work.

In Phase I, highly-nonlinear, finite-element models and a state-of-the-art modeling

strategy are used to validate and verify the geometrically unstable built-up compression

members which exhibit a variety of buckling behaviors. The finite element program ANSYS

is used to validate over 265 experimental tests, while the use of the finite element

program ABAQUS is used to verify the ANSYS results. Two totally different numerical

schemes of implicit-static and explicit-dynamic under various iterative and non-iterative

solution techniques, which include Newton-Raphson, Arc-Length, Riks, and Central-

Difference integration methods, are converged toward identical solutions. A structural

solid (brick) element is thoroughly examined and compared with a structural shell element

(most commonly used in the modeling discipline for thin-walled structures) which

provides advantages in: (1) advancing through a critical buckling state, (2) tracing a softening

response of the post-buckling regime, and (3) assuring the modeling of a true structural

failure (not a numerically induced one).

In Phase II, a parametric study of an additional 360 cold-formed built-up compression

members are modeled to investigate new structural built-up configurations. The AISI

specification flexural provision is applied in conjunction with the slenderness modification

and the code predictions are compared to the results of the analytical models. A proposed design equation is developed based on a regression analysis of a three-dimensional

surface fitting. The proposed equation corrects the deficiency of the distortional provision.

An evaluation of the proposed design equation shows good agreement with the

experimentally measured capacities.
Keywords: Steel--Cold working; Buckling (Mechanics); Strains and stresses; Finite element method; Nonlinear theories